Second Interim Report of the Standing Committee on Inter-sectoral Issues Relating to Tribal Development on Displacement, Resettlement and Rehabilitation of Scheduled Tribes - Planning Commission (Planning Commission, 2007)
The Standing Committee on Inter-Sectoral Issues relating to Tribal Development set up vide notification No.560/03/C/12/2004-ES.II dated 30th October, 2004 of the Prime Minister’s Office (Annexure-I) considered the issue of displacement, resettlement and rehabilitation of Scheduled Tribes affected by various development and other projects, an extremely important one, particularly in the present context, and decided to take it up for detailed examination.
Ministry of Tribal Affairs, Government of India